2008
DOI: 10.1098/rsta.2008.0062
|View full text |Cite
|
Sign up to set email alerts
|

Dumb holes: analogues for black holes

Abstract: The use of sonic analogues to black and white holes, called dumb or deaf holes, to understand the particle production by black holes is reviewed. The results suggest that the black hole particle production is a low-frequency and low-wavenumber process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 20 publications
0
48
0
4
Order By: Relevance
“…Thus, if one could show that for dumb holes the existence of the changes in the theory at short wavelengths did not destroy the existence of thermal radiation from a dumb hole, one would have far more faith that whatever changes in the theory quantum gravity created, whatever nonlinearities quantum gravity introduced into the theory, the prediction of the thermal radiation from black holes was robust. (Unruh 2008(Unruh , p.2908 This is of course a beautiful example of analogical reasoning, perhaps more attractive, but of the same genus to that of Reid. If we could show that the trans-Planckian fluid dynamical effects are irrelevant in our model of the fluid, we could speculate the same may be true with the gravitational case also.…”
Section: Universality and The Hawking Effectmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, if one could show that for dumb holes the existence of the changes in the theory at short wavelengths did not destroy the existence of thermal radiation from a dumb hole, one would have far more faith that whatever changes in the theory quantum gravity created, whatever nonlinearities quantum gravity introduced into the theory, the prediction of the thermal radiation from black holes was robust. (Unruh 2008(Unruh , p.2908 This is of course a beautiful example of analogical reasoning, perhaps more attractive, but of the same genus to that of Reid. If we could show that the trans-Planckian fluid dynamical effects are irrelevant in our model of the fluid, we could speculate the same may be true with the gravitational case also.…”
Section: Universality and The Hawking Effectmentioning
confidence: 98%
“…relationship between frequency and wavenumber) that is relevant to an atomic fluid rather than continuous fluid, and consider whether, in such models, the exponential relationship actually holds between the outgoing wave at some time after the formation of the horizon, and the wavenumber of the wave packet (Unruh 2008). Approximate answers to such questions can be determined in practice via numerical methods, and it was shown by Unruh in 1995 that the altered dispersion relation in atomic fluids does imply that the early time quantum fluctuations that cause the late-time radiation are not in fact exponentially large (Unruh 1995).…”
Section: Universality and The Hawking Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The first examples on the concept of gravity analogues originated in relation to acoustics 84 , as it was shown that supersonic fluid flow can generate an acoustic analogue of a black hole. From then on, several theoretical proposals and experimental works have followed 85,86 . A remarkable aspect of analogue gravity is that non-relativistic phenomena are found to be governed by a curved Lorentzian (pseudo-Riemannian) geometry.…”
Section: �3mentioning
confidence: 99%
“…As a consequence, the mathematical machinery of general relativity proves to be useful in other fields of physics. 8,85,87,88 .…”
Section: �3mentioning
confidence: 99%